Ecological interactions between grain aphids (Sitobion avenae) and Fusarium head blight pathogens (Fusarium graminearum & F. langsethiae) on wheat and their impact on disease - Drakulic, Jassy (2016)
Fusarium head blight pathogens contribute to ear disease in cereals globally, causing yield losses, decreased grain quality, and mycotoxin accumulation in infected grain. Wheat is susceptible to head blight disease after ear emergence, during which time ears can also act as hosts for other biological agents, including insects. Grain aphids, Sitobion avenae, colonise ears preferentially over other tissues of wheat plants, and mutual attack of wheat by grain aphids and Fusarium pathogens is likely to occur in the field. Experiments were conducted to elucidate the nature of the interactions that occur between the plant host, aphid pests and Fusarium pathogens. When aphids had also attacked the host plant, exacerbated disease severity was observed for both Fusarium graminearum and F. langsethiae. Of particular interest was the finding of an increase in mycotoxin accumulation in infected grain when there was aphid herbivory of host plants. Transmission of either species by aphids was not consistently observed, although the apparent compatibility of F. langsethiae with aphid vectors was greater than for F. graminearum. F. langsethiae was transmitted by aphids when moved manually from infected host ears to susceptible healthy ears, but transmission by natural movement of both winged and wingless aphids failed to produce disease in new hosts. In contrast, deoxynivalenol-producing F. graminearum induced the production of volatile host chemicals that repelled aphids, and population dynamics of aphids that colonised wheat ears infected with F. graminearum were impacted negatively, as observed by increased mortality and decreased fecundity of aphids from diseased hosts. The role of mycotoxins in the production of host volatiles was assessed by comparing F. graminearum isolates of different chemotypes, including mycotoxin deficient mutants. In contrast to hosts infected with DON-producing F. graminearum, which produced VOCs that repelled aphids, hosts infected with a nivalenol (NIV)-producing F. graminearum isolate produced VOCs that were attractive to aphids. This response was shown to be due to the mycotoxin production of the pathogen, as a transgenic line of the same isolate deficient impaired in trichothecene production produced no such effect. The importance of timing and location of aphid herbivory relative to the infection site on the development and spread of disease was examined. It was observed that the longer the time of aphid colonisation on hosts prior to the arrival of fungal inoculum, the more severe the consequences of disease for host plants in terms of fungal biomass and visual disease severity. Aphid herbivory on host ears led to a greater increase in disease severity and spread than infestation of leaves. Systemically treated plants also became more vulnerable to elevated pathogen colonisation; however local effects were more influential on disease outcome. The current research findings show the value of considering interactions between plant pathogens and insects. These are usually studied separately but occur together in nature and in this case the insect had a major impact on disease development. This opens questions about how aphids improve host suitability which could be answered by transcriptomic approaches. The study has important practical implications because it suggests that by incorporating traits for resistance to aphids, breeding for FHB resistance could be improved in wheat. Furthermore, control of aphid populations prior to and during heading could reduce the risk of mycotoxin contamination of wheat crops.